"Are You an Immigrant?": Identity‐Based Critical Reflections of Teaching Intercultural Communication. (June 2014) - Chen, Yea‐Wen
Abstract : This chapter examines the negotiated experiences of a female international faculty of color teaching an intercultural communication course from the lens of intersecting cultural identities in the context of a prominently White institution in the United States.